2009
DOI: 10.1016/j.ab.2009.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Assay and purification of ω-amidase/Nit2, a ubiquitously expressed putative tumor suppressor, that catalyzes the deamidation of the α-keto acid analogues of glutamine and asparagine

Abstract: Abstractω-Amidase [ω-amidodicarboxylate amidohydrolase, E.C. 3.5.1.3] isolated from rat liver cytosol is a versatile enzyme that catalyzes a large number of amidase, transamidase and ester hydrolysis reactions. ω-Amidase activity toward α-ketoglutaramate and α-ketosuccinamate (the α-keto acid analogues of glutamine and asparagine, respectively) is present in mammalian tissues, tumors, plants, bacteria and fungi. Despite its versatility, widespread occurrence and high specific activity, the enzyme has been litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
51
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 28 publications
(46 reference statements)
0
51
0
Order By: Relevance
“…Commercially available succinamate [ − O 2 CCH 2 CH 2 C(O)NH 2 ] is the amide substrate, which in the presence of ω-amidase reacts with NH 2 OH to form the corresponding hydroxamate [ − O 2 CCH 2 CH 2 C(O)NHOH]. The hydroxamate in the presence of acidic ferric chloride generates a brown color that can be measured spectrophotometrically (Krasnikov et al 2009a). Hersh (1971Hersh ( , 1972 also showed that the rat liver enzyme has strong esterase activity.…”
Section: Distribution Physical and Enzymatic Properties Of ω-Amidasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercially available succinamate [ − O 2 CCH 2 CH 2 C(O)NH 2 ] is the amide substrate, which in the presence of ω-amidase reacts with NH 2 OH to form the corresponding hydroxamate [ − O 2 CCH 2 CH 2 C(O)NHOH]. The hydroxamate in the presence of acidic ferric chloride generates a brown color that can be measured spectrophotometrically (Krasnikov et al 2009a). Hersh (1971Hersh ( , 1972 also showed that the rat liver enzyme has strong esterase activity.…”
Section: Distribution Physical and Enzymatic Properties Of ω-Amidasesmentioning
confidence: 99%
“…The activity is present in all rat tissues investigated with highest specific activity in liver and kidney (Meister 1953;Cooper 1988) and, as noted above, the activity is present in both cytosolic and mitochondrial fractions. Purification of ω-amidase from rat liver cytosol to homogeneity required a 570-fold enrichment (Krasnikov et al 2009a), which indicates that 0.1-0.2 % of all the soluble protein in the rat liver cytosol is accounted for by this enzyme. We suggest that this high concentration attests to its metabolic importance as a housekeeping enzyme.…”
Section: Distribution Physical and Enzymatic Properties Of ω-Amidasesmentioning
confidence: 99%
“…The resulting hydroxamate is readily quantitated as a brown complex in the presence of highly acidic ferric chloride [45]. In the present work, this procedure was adapted to measure the hydroxaminolysis of l -2-HGM (Equation (10)).…”
Section: Methodsmentioning
confidence: 99%
“…Protein overexpression was induced with 2 mM isopropyl 1-thio-␤-D-galactopyranoside and maintained for 6 h; the overexpressed protein in the crude protein fraction obtained from the periplasmic fraction was further purified. We chose KGM, SM, and 3-PPN for assay of the enzymatic activity of hNit2/-amidase (11,23,31). The proteins were then subjected to kinetic analysis.…”
Section: Methodsmentioning
confidence: 99%
“…A link between cancer biology and the glutaminase II pathway has recently been strengthened by the finding that nitrilase-like protein 2 (Nit2), which was previously shown to be a putative tumor suppressor (22), is identical to -amidase (10,11,23). On the basis of sequence analysis, Pace et al reported that Nit2 belongs to the nitrilase (Nit) superfamily (24,25).…”
mentioning
confidence: 99%